2007
DOI: 10.1128/aem.02823-06
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a 12-Hour TaqMan PCR-Based Method for Detection of Salmonella Bacteria in Meat

Abstract: We developed a 12-h Salmonella detection method, based on 8 h of preenrichment, followed by automated DNA extraction and a sensitive real-time PCR. The method was optimized to obtain the highest possible yield of cells and DNA. The growth of different Salmonella strains in various preenrichment media and the effects of adding growth-promoting and selective reagents were explored, taking into account their PCR compatibility. The effects of (i) analyzing larger volumes (1 to 5 ml) from preenriched samples and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 27 publications
0
63
0
1
Order By: Relevance
“…and S. Enteritidis in environmental samples. VI 1,6,14,25:a:e,n,z15 (CFSAN015097). The DNA extracts from 12 control organisms of a Salmonella panel were prepared from 1.0 ml of overnight culture using InstaGene matrix, according to the manufacturer's instructions (catalog no.…”
Section: Figmentioning
confidence: 99%
“…and S. Enteritidis in environmental samples. VI 1,6,14,25:a:e,n,z15 (CFSAN015097). The DNA extracts from 12 control organisms of a Salmonella panel were prepared from 1.0 ml of overnight culture using InstaGene matrix, according to the manufacturer's instructions (catalog no.…”
Section: Figmentioning
confidence: 99%
“…In addition, as Salmonella in meat is often injured from the chilling process, the international standards recommend a two-step enrichment procedure, where the first nonselective preenrichment step is followed by a selective enrichment step. Several attempts to reduce the enrichment time have been reported (13)(14)(15)(16). Studies in which shortening of the 16-to 20-h reference enrichment time was investigated reported that at least 8 h of incubation was required for meat samples (15,16), while a 3-h incubation resulted in the detection of Salmonella in highly contaminated oysters (17).…”
mentioning
confidence: 99%
“…Several attempts to reduce the enrichment time have been reported (13)(14)(15)(16). Studies in which shortening of the 16-to 20-h reference enrichment time was investigated reported that at least 8 h of incubation was required for meat samples (15,16), while a 3-h incubation resulted in the detection of Salmonella in highly contaminated oysters (17). Omitting the time-consuming enrich-ment step would therefore be optimal, and several direct detection methods have also been published (9,(18)(19)(20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An additional centrifugation step just prior to the PCR reaction was suggested by Chen et al (1997) to better remove PCR inhibitors. Wilson (1997) recommended a washing step to reduce the fat and other residues in foods which could inhibit the PCR reaction, whereas Josefsen et al (2007) reported lower reproducibility with the washing step. Immunomagnetic separation (IMS) with an additional enrichment step was used to overcome false-negative results of Salmonella in chicken products (Soumet et al, 1997).…”
Section: Discussionmentioning
confidence: 99%